2009
DOI: 10.1007/s12272-009-2210-1
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of Human Burkitt’s lymphoma cells induced by 2-N,N-Diethylaminocarbonyloxymethyl-1-diphenylmethyl-4-(3,4,5-trimethoxybenzoyl) piperazine hydrochloride (PMS-1077)

Abstract: Piperazine is one of the heterocycles which are associated with diverse pharmacological activities. 2-N,N-Diethylaminocarbonyloxymethyl-1-diphenylmethyl-4-(3,4,5-trimethoxybenzoyl) piperazine hydrochloride (PMS-1077) is a trisubstituted piperazine which contains a trimethoxybenzene ring and a benzhydrylpiperazine fragment, both of which can induce cell proliferation regression by different mechanisms. We have therefore examined the effects of PMS-1077 on Human Burkitt's lymphoma cells (Raji). The viability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…To observe the morphological changes in apoptotic cells, the AO and EB staining was performed [10] . Briefly, cells were harvested with 0.125% trypsin and 0.01% EDTA, re-suspended in 95 μL of RPMI-1640 medium, and incubated with 5 μL of AO/EB staining solution (100 mg/L PBS with each dye) at room temperature for 15 min.…”
Section: Ao/eb Fluorescent Stainingmentioning
confidence: 99%
“…To observe the morphological changes in apoptotic cells, the AO and EB staining was performed [10] . Briefly, cells were harvested with 0.125% trypsin and 0.01% EDTA, re-suspended in 95 μL of RPMI-1640 medium, and incubated with 5 μL of AO/EB staining solution (100 mg/L PBS with each dye) at room temperature for 15 min.…”
Section: Ao/eb Fluorescent Stainingmentioning
confidence: 99%
“…While further improving these properties and taking into account the flexibility of these compounds, we were also engaged to study the potential effects of these compounds in other pathological conditions, such as inflammation and tumor genesis. Our previous work demonstrated that PMS1077 could induce apoptosis of Raji cells, but the mechanism of action remains unclear [5].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 2, all tested compounds were screened with mean 50% growth inhibition concentration (GI 50 ) in micromolar concentration range.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…It can be noted that thioamides show higher activity than their carboxamide derivatives, which can be exemplified by compounds 5j (GI 50 The most active compounds against MCF-7 cell line are 5u (GI 50 ¼ 6.14 mM) and 6e (GI 50 ¼ 4.94 mM). Furthermore, we observed that compound 6e was less toxic in MCF-12A (GI 50 ¼ 8.5 mM), which is a normal-like breast epithelial cell line (Table 4).…”
Section: Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation